Porous Chambers, Echoes of Valence and Stereotypes: A Network Analysis of Online News Coverage Interconnectedness Following a Nationally Polarizing Race-Related Event. Issue 2 (March 2018) - Turetsky, Kate M.; Riddle, Travis A.
Selective exposure to one-sided news coverage, especially of controversial geopolitical events, may contribute to growing social polarization. Existing research on "echo chambers"—fragmented information environments that amplify homogeneous perspectives—focuses on the degree to which individuals and social media platforms shape informational segregation. Here, we explore whether news organizations directly contribute to echo chambers through the hyperlinks they embed in online articles. Using network and text analysis, we examined coverage of the 2014 shooting of Michael Brown in Ferguson, MO, and found that online news media exhibited weak community structure and high connectivity across news outlets. However, analyses also indicated that media sources were more likely to link to coverage that was similar to their own in terms of emotional valence and stereotype-relevant aspects of the events. While hyperlinking to diverse news sources may ameliorate fragmented information environments, selectively linking to similar coverage may contribute to growing polarization.